Geographies of Policy Mobilities. Issue 5 (30th May 2013) - Temenos, Cristina; McCann, Eugene
Abstract: This article reviews geographic literature on policy mobilities. It outlines the emergence of the policy mobilities, mutations, and assemblage approach, and the geographic, sociological, and political science literatures from which it draws its origins. Focusing attention on the interplay between the structuring fields of the policy transfer and the policy actors who are ultimately responsible for the construction, conceptualization, adoption, education around, and implementation of policies, this article charts work that has focused on the mechanisms through which policies are mobilized, altered, and touched down in various places and how these processes shape cities. It concludes with commentary on possible future directions, both empirical and conceptual, that the policy mobilities approach might take and note the various methodological contributions that are emerging from it.